Evaluation Of Pole and Line Fisheries Business Performance at The Dufa-Dufa Fish Landing Base, Ternate City North Maluku Province - Kaidati, Bahar; Karman, Amirul; H Iksanan, Kusdi; Abdullah, Yasmin Abdullah (Agrikan Jurnal Agribisnis Perikanan, 2022)
The pole and line fishery business at the Dufa-Dufa fish landing base (PPI) in Ternate City generally uses FADs. Based on information from fishermen, the type of fishing gear has developed relatively quickly to become semi-industrial, as indicated by the increase in fishing capacity (vessel size and engine power included) and the expansion of fishing areas, as well as the use of FADs. This is because the influence of production inputs is needed so that the fishing effort runs optimally. The effective and efficient use of production inputs can increase the catch and income of fishermen. Therefore, the research was designed with the aim of evaluating the performance of the pole and line fishery business which includes technical, biological, and economic aspects. The research was carried out at PPI Dufa-Dufa, from June to July 2021. The study used a descriptive survey method. The results showed that the fishing gear used to catch skipjack tuna, yellowfin tuna and tuna in the Ternate City waters was the pole and line. The trend of catch production, fleet productivity, and FAD productivity for 5 years (2016-2020) is increasing. This fishing business is profitable and deserves to be continued. Financially (profits) and investment (Net B/C, IRR, BEP, and PP) the pole and lien fishery business based at PPI Dufa-Dufa is profitable and feasible to operate throughout the year with a profit value ranging from IDR. 436,576,400,000-498,528,000.00, the value of B/C ratiao 1.01-1.39, IRR 32%-38%, BEP IDR. 2,805,673,599.97-3,247,175,999.96, and PP 2.43-3.03 years.